English proficiency vs. professionalism : a case study of perceived management of linguistic diversity in an international organization - Kalenius, Netta (2019)
The role, complexity and effects of language in international business are greatly acknowledged, but this is yet to show in research (Piekkari, Welch & Welch, 2014: 9). The purpose of the paper is to get an understanding of the extent to which one’s English proficiency affects the perceived professionalism and competence in one’s job. In addition, this case study looks into the management of linguistic diversity in an international organization, the case company. The research questions are: 1) How do professionals relate language proficiency to perceived professionalism? and 2) How is linguistic diversity approached and managed in a multilingual work place?